The posttreatment mean apparent diffusion coefficient of primary tumor is superior to pretreatment ADCmean of primary tumor as a predictor of prognosis with cervical cancer. (16th June 2013) - Nakamura, Keiichiro; Kajitani, Satoshi; Joja, Ikuo; Haruma, Tomoko; Fukushima, Chikako; Kusumoto, Tomoyuki; Seki, Noriko; Hiramatsu, Yuji
Abstract The objective of this study was to investigate the correlation of pretreatment and posttreatment measurements as the mean apparent diffusion coefficient (ADCmean) by diffusion‐weighted magnetic resonance imaging (DWI) findings with prognostic factors in patients with squamous cell carcinoma (SCC) of primary cervical cancer. The pretreatment and posttreatment ADCmean of the primary tumor were examined for their correlations with the prognosis in 69 patients with SCC of primary cervical cancer by radiotherapy (RT) with or without concurrent chemotherapy (CCRT). The median disease‐free survival (DFS) and overall survival (OS) times of patients were 20.97 and 23.47 months (follow‐up periods for DFS and OS: 1–72 and 1–72 months). The DFS and OS rates of patients with low pretreatment and posttreatment ADCmean of the primary tumor were also significantly worse than those of patients exhibiting high pretreatment and posttreatment ADCmean of the primary tumor (DFS; P = 0.0130 and P < 0.0001, OS; P = 0.0010 and P < 0.0001). Multivariate analyses showed that low posttreatment ADCmean of the primary tumor was an independent prognostic factor for DFS and OS (P < 0.0001 and P < 0.0001). The low posttreatment ADCmean of the primary tumor is a useful clinical prognostic biomarker for recurrence and survival in patients with cervical cancer.